The complete chloroplast genome of Rhus punjabensis var. sinica. Issue 1 (2nd January 2022) - Pan, Yunjia; Feng, Jinglu; Lin, Yulin; Yao, Hui
Abstract: Rhus punjabensis var. sinica belongs to the family Anacardiaceae in the order Sapindales. In this study, we first reported the complete chloroplast genome sequence of R. punjabensis var. sinica . The cp genome was sequenced on Illumina Hiseq 2000 platform. The sequence was found to be 159, 617 bp in length with 37.9% GC contents, including a large single-copy region of 87, 694 bp, a small single-copy region of 18, 971 bp, and a pair of inverted repeats of 26, 476 bp. The chloroplast genome of R. punjabensis var. sinica contains 133 genes, including 86 protein-coding genes, 8 rRNA genes, and 2 pseudogenes identified by CPGAVAS2 and BLAST search, and 37 tRNA genes annotated by tRNAscan-SE. Maximum-likelihood (ML) phylogenetic analysis showed that R. punjabensis var. sinica was sister to Rhus potaninii .